1989
DOI: 10.1002/anr.1780321213
|View full text |Cite
|
Sign up to set email alerts
|

New radiographic grading scales for osteoarthritis of the hand. Reliability for determining prevalence and progression

Abstract: We developed and evaluated scales for grading the prevalence and progression of the individual radiographic features of osteoarthritis (OA) of the hand. Four equally time-spaced hand radiographs from 50 participants in the Baltimore Longitudinal Study of Aging, who were followed for at least 20 years, were read separately and "blindly" by 4 experienced, trained readers. Eleven hand joints were individually assessed for the presence of osteophytes, joint space narrowing, subchondral cysts, subchondral sclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
0
6

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(110 citation statements)
references
References 9 publications
1
103
0
6
Order By: Relevance
“…On each hand radiograph, individual joints were graded for the presence and severity of 5 selected individual features of OA: osteophytes, joint space narrowing, subchondral sclerosis, lateral deformity, and cortical collapse (21). Osteophytes and joint space narrowing were differentiated into 4 ordinal grades (grades 0, 1, 2, and 3), while sclerosis, lateral deformity, cortical collapse, and narrowing of the first carpometacarpal (CMC I ) joint were scored as either absent or present.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On each hand radiograph, individual joints were graded for the presence and severity of 5 selected individual features of OA: osteophytes, joint space narrowing, subchondral sclerosis, lateral deformity, and cortical collapse (21). Osteophytes and joint space narrowing were differentiated into 4 ordinal grades (grades 0, 1, 2, and 3), while sclerosis, lateral deformity, cortical collapse, and narrowing of the first carpometacarpal (CMC I ) joint were scored as either absent or present.…”
Section: Methodsmentioning
confidence: 99%
“…All radiographs were read individually in random sequence and were not paired. Readings were performed over a 3-week period by 1 experienced reader (DAK); interreader reliability of DAK's interpretations compared with those of others (FMW, WWS, and MCH) and intrareader reliability over time had previously been established (21). A subset of the radiographs read for this study had also been read 8 months earlier by the same reader, and the intrareader reliability on this subset was good to excellent for all scales (intraclass correlation coefficient 0.66-0.93) (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sensitive methods of assessing the evolution of finger joint OA within rather short evaluation periods have been described (10,l l), conventional roentgenograms remain the best available method of following patients with OA in daily practice. Single bilateral posteroanterior (PA) hand radiographs are considered sensitive enough to assess finger joint OA (12,13).…”
mentioning
confidence: 99%
“…(9) Radiographic features of osteoarthritis are often seen in the hands, especially in elderly patients, in the absence of symptoms, and so may represent age-related changes. (10) Kessler et al (11) suggested a hand scale for osteoarthritis in which radiological osteoarthritis is defined only when joint space narrowing is present. To determine the nature and severity of osteoarthritis in hand joints, several standardized qualitative scoring methods can be used, including those described by Kellgren and Lawrence, (12) …”
Section: Introductionmentioning
confidence: 99%